Immune Reactions of Human Blood Platelets - Mueller-Eckhardt, Ch; Lüscher, E. F (Thrombosis and Haemostasis, 1968)
The effect on human platelets of 2 endotoxin preparations (one had known Shwartzman-activity in rabbits, the other was not tested for its biological activity) was investigated in vitro. The following results were found:1. Endotoxin has no effect on washed human platelets suspended in isotonic, plasmafree buffer solution.2. Aggregation or release of adenine nucleotides from human platelets by endotoxin does also not occur if the platelets are suspended in coagulable, complement active, pooled human plasma or plasma fractions.3. Platelets pretreated with α-chymotrypsin do not show aggregation or release of nucleotides by endotoxin.4. The ability of human platelets to retract a fibrin clot is not disturbed by endotoxin. This excludes a functional platelet injury by endotoxin not detectable by aggregation or nucleotide release.5. There is no evidence for the assumption that the effect of endotoxin on platelets is transmitted by yet hypothetical, platelet-damaging mediator substances from leukocytes.6. These results suggest that an immunological injury of platelets by endotoxin comparable with the effect of immune complexes or aggregated gammaglobulin is highly improbable.